THE ANTHROPOGENIC CHANGES IN THE GEOLOGICAL ENVIRONMENT IN THE SOUTH OF EAST SIBERIA - Kozyreva, E.A; Khak, V.A. (Bulletin of the Geological Society of Greece, 2010)
The investigation results of the geological environment’s condition in an areas marked by high anthropogenic load are described in this paper. In the southern East Siberia the strategy of key sites monitoring is used for this purpose. The selection of key sites is determined by the specific character of geological environment, as well as by the intensity and relationships of developing geological processes. In the studied territory the great variety of exogenic processes can be observed, the majority of them being activated by technogenic factors. To the inherited processes the gravitation, cryogenic and those induced by surface and subsurface water activity belong. In order to estimate the actual condition of the territories and to ensure the undisturbed exploitation of engineering structures, the specific features of lithosphere, the development of exogenic geological processes and the evolution of the anthropogenesis should be taken under consideration.